Antibiotic Susceptibility of Staphylococcus Aureus with VanA and MecA Genes - Ghimire, Lata; Banjara, Megha Raj; Abdulla, Abdelkodose MH (Journal of Nepal Health Research Council, 2024)
Background: Staphylococcus aureus (S.aureus) is an emerging antibiotic resistant bacterium responsible for various infections in human. Resistance to methicillin and vancomycin are of prime concern in S. aureus. The study aims to determine the minimum inhibitory concentration (MIC) of Vancomycin and evaluate the existence of mecA and vanA genes, associated with antibiotic resistance.Methods: Clinical specimens from three Kathmandu hospitals were processed and S. aureus was identified using conventional microbiological procedures. MRSA was phenotypically identified with cefoxitin (30µg) disc diffusion, while vancomycin susceptibility was assessed using the Ezy MICTM stripes. The mecA and vanA genes were detected by polymerase chain reaction (PCR). Results: Out of 266 S. aureus samples from various clinical specimen subjected for analysis, 77 (28.9%) were found methicillin-resistant (MRSA) and 10 (3.8%) were observed vancomycin-resistant (VRSA). Vancomycin resistant isolates showed a significant correlation between resistance to ampicillin, chloramphenicol, and cefoxitin. The mecA gene was found in 39 of the MRSA isolates, having 50.64% of MRSA cases, while the vanA gene was detected in 4 of the VRSA cases, constituting 40% of VRSA occurrences.Conclusions: The strains with higher vancomycin minimum inhibitory concentration values (? 1.5 ?g/ml) displayed increased resistance rates to various antibiotics compared to strains with lower minimum inhibitory concentration values (< 1.5 ?g/ml). The presence of vanA genes was strongly associated (100%) with vancomycin resistance, while the 10.3% mecA gene was identified from MRSA having resistance towards vancomycin also.Keywords: Methicillin resistance; minimum inhibitory concentration; staphylococcus aureus; vancomycin resistance.